(untitled) (Research, Society and Development, 2021)
The recovery of organic fertilizers from human urine as one of the solutions for the sustainable management of effluents and sanitation can be very promising, by the strategy of reuse urban wastewater, combined with the development of agricultural input. The aim of this study was to conduct a bibliometric analysis of the publications available in the ScienceDirect and Wiley Online Library databases on the subject of human urine nutrient recovery for the period from 1999 to 2020 to respond whether human urine recycling can improve cities resilience, through urban water management has the potential to become a competitive solution in the Agri-Food global market based on scientific findings. The process of bibliometric analysis exploring databases were divided in 8 steps: 1) Key-word selection, 2) Period selection, 3) Database selection, 4) Scanning the publications, 5) Removal of duplicates, 6) Verification of publications, 7) Selection of the publications with the highest adherence, 8) Final classification. A total of 985 scientific publications were selected from the Wiley Online Library and 996 from Science Direct. Out of these, only 45 were selected for being potentially aligned with urine recycling technologies relate to water management in a worldwide perspective. Human urine as a bio-fertilizer has the potential to the Agribusiness market, based on statistical data analysis, however to become a marketable product, especially in low-middle income countries, sustainability assessment studies of urine technologies, integrating economic, social and environmental aspects are needed.